The Effectiveness of Contextual Problem Based Learning Model and Personality Types on Students History Learning Outcomes - Loppies, Megiridha; Kulyasin; Ayesma, Pamela (Universitas Pendidikan Ganesha, 2024)
Learning outcomes are one of the important factors that used to measure persons success in learning. This study aims to analyze the effectiveness of contextual problem-based history learning models and personality types on student history learning outcomes between groups of students using contextual problem-based learning models and groups of students using conventional learning models involving personality types in XI IPS class at senior high school. The method used in this study was a quasi-experimental quantitative with a 2x2 treatment design model. The population in this study was all students of XI IPS class consisting of four class, totaling 124 students. The research sample was determined by purposive random sampling technique. The data were collected using the test method to measure student learning outcomes and the questionnaire was used to measure the student's personality type. The results showed that the learning outcomes of students who use contextual problem-based learning models are higher than students who use conventional learning models. There is an interaction effect between contextual problem-based learning models and personality types on history learning outcomes. The learning outcomes of students with extrovert personality types who use contextual problem-based learning models are higher than students who use conventional learning models. The learning outcomes of students with introverted personality types who use contextual problem-based learning models are lower than students who use conventional learning models.